Bacteriological Studies with Morphine-Like Narcotics: Relevance to Narcotic Actions in Mammals? - Wolfe, Alan D. (1975)
A search for active bacterial growth inhibitors among seven highly potent morphine-like narcotics revealed that NIH 7591 and etorphine inhibited the rates of growth of Escherichia coli by 50% at 1.9 × 10(−4) M. Bacterial cultures escaped from growth inhibition by NIH 7591 after times which were proportional to the drug concentrations and inversely proportional to the initial bacterial densities. Populations of E. coli could adapt to resist and cross-resist growth inhibitions by NIH 7591 and phenazocine. Resistance was lost after growth in drug-free medium for a few doubling times. The agonist-antagonist pair, etorphine and diprenorphine, inhibited growth of E. coli additively without any indication of antagonism. Actions of narcotics in bacteria is considered a theme in its own right.